THE COMMERCIAL DYNAMICS OF AIN MLILA (ALGERIA). NUMEROUS SPATIAL REFLECTIONS AND SUPPORTING ELEMENTS - Houssem Elddine Berkani; Salah Bouchemal; Aissa Boulkaibet (International Journal of Innovative Technologies in Social Science, 2024)
The unmistakable area of Ain Mlila city within the heart of the Constantine tall fields, at the crossing point of National Street 03 and National Street 100, and close major urban centers in eastern Algeria (Constantine, Batna, Setif...), played a significant part in its development and commercial and urban renaissance. It changed from a little provincial settlement with 12 shops in 1869 to a dynamic urban and commercial center with 16791 shops in 2020 (Commercial Registry Office of Oum El Bouaghi Wilaya, 2022), generally claimed by neighborhood dealers at 60%, with a clear specialization in car save parts speaking to 44.3% of add up to commercial action shops, agreeing to a field consider conducted amid the investigate. Family and tribal systems, and universal openness to worldwide commercial markets in Africa, Europe, and Asia, played a essential part in quickening development and commercial improvement forms. This made a commercial energetic reflected in engaging quality for both dealers and clients, which affected numerous other urban factors, whether spatial-urban or statistic. The city seen an astonishing statistic change, with its populace expanding from 5063 tenants in 1954 (Common Populace and Lodging Census, Common Government of Algeria, 1954) to 116641 occupants in 2020, agreeing to gauges from the Respectful Status Office of Ain Mlila Municipality. Commercial exercises differentiated to incorporate nourishment exchange at 30.3%, clothing and footwear exchange at 19%, with car save parts exchange overwhelming. Commercial hones were dispersed between retail deals (49.4%), discount deals (28.2%), and semi-wholesale deals (22.4%) (Field consider, 2023). The Ain Mlila demonstrate reflects the capacity of Algerian cities to use their topographical characteristics and social properties to realize nearby improvement based on commercial action advancement, profiting from their openness to worldwide markets and their capacity to adjust to quick financial changes.